2023
DOI: 10.1108/agjsr-09-2022-0163
|View full text |Cite
|
Sign up to set email alerts
|

Job performance, knowledge and perceived power of tax officers on tax morale amongst agrochemical traders in Ghana

Abstract: PurposeThe paper aims to examine agrochemical traders’ tax morale in three Ghanaian regions.Design/methodology/approachPrimary data were collected from 92 respondents using structured questionnaires. A multistage sampling technique was employed and used in selecting respondents.. Descriptive statistics, factor analysis and quantile regression analysis were used to analyse data obtained via the questionnaires.FindingsThe study found tax reporting knowledge, tax calculating knowledge and tax payment knowledge to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…This contradicts research (Radwan & Khalil, 2021) showed the positive influence of knowledge on their support for sustainability. Another study (Kumi & Bannor, 2023) also found that knowledge positively affects individual behavior. Although it does not directly affect students, knowledge resulting from student learning is essential and must be considered.…”
Section: Agjsrmentioning
confidence: 88%
“…This contradicts research (Radwan & Khalil, 2021) showed the positive influence of knowledge on their support for sustainability. Another study (Kumi & Bannor, 2023) also found that knowledge positively affects individual behavior. Although it does not directly affect students, knowledge resulting from student learning is essential and must be considered.…”
Section: Agjsrmentioning
confidence: 88%
“…Previous studies have focused on a review of agrochemicals usage and the Ghanaian Environment (Fianko et al, 2011), an examination of the regional policies governing pesticide application in the nation (Ghana precisely) (Diarra and Tasie, 2017), tax policy and farm capital investment (Williamson & Stutzman, 2016), the impact of the threat on tax compliance (Mohdali, Isa, & Yusoff, 2014), SMEs' attitudes towards tax compliance in Zimbabwe (Nyamwanza, Mavhiki, Mapetere, & Nyamwanza, 2014), To Pay or Not to Pay? Citizens' Attitude Towards Taxation in Kenya, Tanzania, Uganda and South Africa (Ali, Fjeldstad, & Sjursena, 2014), underreporting of income among the self-employed in Europe (Kukk, Paulus, & Staehr, 2020), and job performance, knowledge and perceived power of tax officers on tax morale of agrochemical traders in Ghana (Kumi & Kwasi Bannor, 2023). Hence, this study fills the gap by touching on the determinants of voluntary and enforced tax compliance among agrochemical traders.…”
Section: Agjsrmentioning
confidence: 96%
“…A prevailing agreement in tax compliance research highlights the important role of a fair tax system in shaping taxpayers' compliance behavior (Taing and Chang 2020;Nguyen 2022;Inasius 2019a). Therefore, education on taxation has a positive impact on tax knowledge (Kumi and Kwasi 2023;Gunaasih 2022), leading to a positive influence on the perceptions of tax fairness, which in turn significantly contributes to enhanced tax compliance, Mukhlis et al (2015).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…To build a new tax culture centered on a "culture of tax compliance" means educating taxpayers to perceive tax payments as an integral part of their relationship with the government, built upon rights and responsibilities (OECD 2021). Tax education plays a critical role in promoting voluntary tax compliance, enhancing taxpayer understanding of the tax system, improving their perceptions of the tax system's fairness, and building trust in tax authorities, leading to more effective compliance and enforcement (Mukhlis et al 2015;Gunaasih 2022;Kumi and Kwasi 2023). Merely informing taxpayers about their tax obligations falls short (Moore 2019;Craig and Slemrod 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation